Afiwe Akoonu Ajemo-Eko-Iwa-Omoluwabi ni Awujo Yoruba ati Hausa Bi O Se Han Ninu Orin Orlando Owoh ati Dan Maraya Jos (A Comparative Study of the Ethical Values of the Yoruba and Hausa as Reflected in the Songs Of Orlando Owoh and Dan Maraya Jos). - Adesokan, Sunday Lawrence (2015)
This study analysed and contrasted the content of the songs of Orlando Owoh and Dan Maraya Jos, using them to identify the similarities and differences in the ethical values of the Hausa and Yoruba ethnic groups. In addition, the study explored their socio-cultural environments which gave the compositions the fame and acceptance they enjoyed. The themes inherent in the songs of the two artistes were also analysed.